(untitled) (Research, Society and Development, 2021)
A production chain refers to the set of successive stages of interconnected operations through which different inputs undergo some transformation process until the composition of a final product. This article aims to study the management of the beef production chain in the Municipality of Dianópolis / TO, from the analysis of transportation, processing, processing, marketing and distribution activities to the final customer, in the period from February 1st to October 30, 2020. The research has a descriptive and exploratory character, the methodology chosen is qualitative and quantitative, carried out through bibliographic, documentary, field and case study research. The data collection instruments were; two questionnaires, the first structured, mixed with ten questions, applied to 13 cattle breeders in Dianópolis, the second semi-structured, with five open questions, sent to the Slaughterhouse manager. The questionnaires were sent to the participants’ e-mail using the Google forms. The interviews were carried out in the period between 10 and 30 October 2020. In the study it was found that the Municipality of Dianópolis, has 543 producers. 553 rural properties and 52,844 cattle heads, 76.92% of the interviewed producers stated that they sell the cattle to the local slaughterhouse. The processing of beef production is the transportation, rest, washing, hanging of bleeding, skinning, evisceration, cuts of the carcass, refrigeration, cutting and deboning, packaging, storage and shipping of the meat.